Register Bahasa dalam Iklan Sepeda Motor di Radio JPI FM - Norcholifah, Anisa; Oktavia, Wahyu (Universitas Mathla'ul Anwar Banten, 2019)
The research was conducted with the aim to describe: (1) forms of language registers used in motorcycle advertisement on JPI FM radio; 2) the factors that cause the emergence of registers in motorcycle ads on JPI FM radio. Data retrieval is done by listening and recording. In data analysis techniques, researchers used qualitative methods. Technique of presentation of result of data analysis used is method of informal presentation because its data is speech. Based on the results of data analysis, it can be concluded that there is a language register in a motorcycle advertisement on JPI FM radio consisting of a sentence abbreviated one of which is the mokas stands from used motor. It also found the register in the ad sentence that uses the Java language as a characteristic. In the formation of registers on motorcycle advertisements on JPI FM radio is also influenced by several factors namely social factors, culture, and language.Keywords: Register, Motorcycle Ad, and FM JPI Radio